1994
DOI: 10.1111/j.1365-2605.1994.tb01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of epididymal sperm maturation in the golden hamster

Abstract: During passage of hamster spermatozoa through the epididymis their maturation is shown to involve changes in the sperm head, midpiece (mitochondria) and tail. The sum of these changes results in a dramatic increase in the fertilizing potential of the spermatozoa. When comparable numbers of spermatozoa from the caput or corpus epididymis were injected into one uterine horn of mature females, following ovulation induction, and spermatozoa from the cauda epididymis were injected into the contralateral horn, no fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Its expression was somewhat reduced in the distal cauda, and only low expression was found in the caput region. The highest percentage of nonviable spermatozoa is also found in the cauda region (15), suggesting a role for fgl2 in the protection of mature spermatozoa. Previous histological studies of the guinea pig and rat have identified eosinophilic masses containing degenerating spermatozoa within the epididymal lumen (12,13,37).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Its expression was somewhat reduced in the distal cauda, and only low expression was found in the caput region. The highest percentage of nonviable spermatozoa is also found in the cauda region (15), suggesting a role for fgl2 in the protection of mature spermatozoa. Previous histological studies of the guinea pig and rat have identified eosinophilic masses containing degenerating spermatozoa within the epididymal lumen (12,13,37).…”
Section: Discussionmentioning
confidence: 94%
“…Although the cauda epididymidis promotes their survival, the presence of dead spermatozoa in this region has been observed in many species (12)(13)(14)(15). Degenerating spermatozoa release enzymes that may compromise the viability of neighboring cells and represent a source of autoantigens that could provoke an immune response if they escaped from the epididymal lumen.…”
mentioning
confidence: 99%
“…For example, spermatozoa from both the caput epididymis and the proximal corpus epididymis lack the ability to fertilize; whereas, spermatozoa from the distal corpus epididymis and the cauda epididymis have this ability [8,13,14]. Human spermatozoa in which the chromatin is not completely condensed are also reported to have a low percentage of fertilization [15].…”
Section: Introductionmentioning
confidence: 99%
“…The weight ratio of epididymidis/testis increased from 0.1 at 30 dpp to approximately 0.3 at 70d pp (Table 1). The late development of the epididymidis may explain the lack of fertilizing ability of cauda epididymal sperm from early pubertal hamsters (Weissenberg et al, 1987(Weissenberg et al, , 1994(Weissenberg et al, , 1995. Miething (1998) has reported that the enzyme, 11-betahydroxysteroid dehydrogenase, which promotes testosterone output, appears in testicular Leydig cells at about 30 dpp, suggesting that the sigmoidal increase in epididymal weight may be correlated with rising androgen concentrations.…”
Section: Resultsmentioning
confidence: 96%
“…Cortadellas and Durfort (1994) reported that cytoplasmic droplet of hamster epididymal spermatozoa contained ribosomes. Weissenberg et al (1994) found that a cytoplasmic droplet was found associated with the sperm neck in the hamster caput epididymidis and with the tail in the cauda epididymal sperms. It is possible that ribosomes were lost during sperm epididymal transit.…”
Section: Resultsmentioning
confidence: 97%